Ecological Engineering: A Practice to Conserve Pollinators and Natural Enemies - Asritha, Chava; Ramesha, N. M.; Satwika, Maharaj; Kumar, Methuku Anil; Priyanka, N.; Bharghavi, K. (Chronicle of Bioresource Management, 2024)
Intensive agriculture has significantly impacted beneficial arthropods, such as natural enemies and pollinators, through practices like excessive pesticide use and habitat reduction. The disruption has led to declines in biological diversity and ecosystem services provided by organisms, undermining agroecosystem sustainability. Ecological engineering offers a promising solution by fostering balanced ecosystems through biodiversity enhancement and habitat manipulation. This approach includes methods such as trap cropping, intercropping, and the use of flower strips to manage pests and support pollinators. Trap cropping diverts pests from main crops to trap crops, reducing damage and reliance on pesticides. Intercropping reduces pest pressure by dividing pest populations and enhancing natural enemy habitats. Flower strips provide essential resources for natural enemies, boosting their effectiveness. Border crops act as physical barriers and provide additional resources for pest control. Non-cropped areas enhanced with floral resources and cover crops support pollinators. Integrating ecological engineering principles achieves sustainable pest management, benefiting agricultural productivity and pollinator conservation.